2005
DOI: 10.1007/s11199-005-3710-1
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Double Standard: Portrayals of Age and Gender in Popular Films

Abstract: An analysis of the top 100 domestic grossing films of 2002 found evidence of a lingering double standard for aging female and male characters. Overall, major male characters outnumbered major female characters (73% vs. 27%); the majority of male characters were in their 30s and 40s, and the majority of female characters were in their 20s and 30s. Both women and men in their 60s and older were dramatically underrepresented compared to their representation in the US population. For male characters, leadership an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(75 citation statements)
references
References 29 publications
4
67
0
4
Order By: Relevance
“…Moreover, older female characters have been represented as older at a much younger age than male characters, and, correspondingly, they have been represented as much older than male characters of the same age (Signorielli, 2001(Signorielli, , 2004Lauzen & Dozier, 2005;Lauzen, Dozier & Rayes, 2007;Barrett, Raphael & Gundersson, 2014;Women's Media Center, 2014, 2015Lauzen, 2016). Finally, in the wake of the seminal study by Gerbner et al (1980) of the misrepresentation of older people in the media, a range of studies has shown how negative representations of older people not only infl uence general attitudes toward older people but also older people's self-perception (for an overview, see Barrett, Raphael & Gundersson, 2014).…”
Section: Invisibility and Hypervisibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, older female characters have been represented as older at a much younger age than male characters, and, correspondingly, they have been represented as much older than male characters of the same age (Signorielli, 2001(Signorielli, , 2004Lauzen & Dozier, 2005;Lauzen, Dozier & Rayes, 2007;Barrett, Raphael & Gundersson, 2014;Women's Media Center, 2014, 2015Lauzen, 2016). Finally, in the wake of the seminal study by Gerbner et al (1980) of the misrepresentation of older people in the media, a range of studies has shown how negative representations of older people not only infl uence general attitudes toward older people but also older people's self-perception (for an overview, see Barrett, Raphael & Gundersson, 2014).…”
Section: Invisibility and Hypervisibilitymentioning
confidence: 99%
“…Moreover, Lauzen and Dozier (2005) found in their 2002 study of representations of diff erent age groups in top-grossing fi lms that women over the age of 60 made up 8% of characters but 22% of the entire population (in contrast, women aged 30-39 made up 32% of fi lm roles but only 18% of the US population); in addition, in the 2004 study by Lauzen, Dozier and Rayes (2007), women accounted for 26% and men 74% of characters over 60 in prime time television. Most recently, in "Th e Status of Women in the Media 2014 Report", female characters over 65 made up only 3.7% of all characters in the top-grossing fi lms from 2012.…”
Section: Invisibility and Hypervisibilitymentioning
confidence: 99%
“…Kadın spikerler ise, özellikle çok güzel ve gençtir ancak bu özellikleri onlara erkekler kadar otoriter ve deneyimli bir hava katmamaktadır. Sonuç olarak toplum tarafından ciddiye alınan haber programlarında yer alan toplumsal cinsiyet farklılıkları, yetişkinlerin ve özellikle toplumsal cinsiyet kimliklerinden ve rollerinden emin olmaya çalışan ve bu amaçla destekleyici bir güdü arayan çocukların fikirlerinde etkili olmaktadır (Lauzen & Dozier, 2005 (Orhon, 2010).…”
Section: Televizyon Programlarında Toplumsal Cinsiyet Mesajlarıunclassified
“…Toplumun tüm bireyleri tarafından izlenebilen filmlerde de diğer programlara benzer olarak erkekler; sabırlı, dominant, özgür, becerikli, başarılı iken kadınlar; anne, erkeğe bağımlı, âşık, duygusal olarak yansıtılmışlardır (Lauzen & Dozier, 2005).…”
Section: Televizyon Filmlerinde Toplumsal Cinsiyet Mesajlarıunclassified
See 1 more Smart Citation